2020
DOI: 10.31348/2020/3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Purpose: Amblyopia is one of the most common childhood disease. The average prevalence of amblyopia in children is estimated at 2-5 %. It arises during the child development until the age of six, if not treated then, it persist throught adulthood. The aim of our work is to retrospectively analyze the results of treatment of anisometropic amblyopia using dichoptical training in virtual reality in adult amblyopic patients. Materials and Methods: Our group consisted of 84 amblyopic patients with anisometropic am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Performance ease of participants has shown that the headsets achieved acceptable compliance when used as a training tool. 46 , 47 , 56 , 58 , 71 As reported by Waddingham et al, 84 Cleary et al, 86 Herbison et al, 87 Herbison et al, 88 Vedamurthy et al, 45 Hurd et al, 53 Halička et al, 55 Jhangian et al, 58 Tan et al, 60 and Xiao et al, 89 VA outcomes have shown comparable improvements through training using VR applications. Likewise, Rajavi et al, 49 Žiak et al, 16 Elhusseiny et al, 69 and Rajavi et al 50 have also made VA improvements, which reflected a promising application value for further research on this topic.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Performance ease of participants has shown that the headsets achieved acceptable compliance when used as a training tool. 46 , 47 , 56 , 58 , 71 As reported by Waddingham et al, 84 Cleary et al, 86 Herbison et al, 87 Herbison et al, 88 Vedamurthy et al, 45 Hurd et al, 53 Halička et al, 55 Jhangian et al, 58 Tan et al, 60 and Xiao et al, 89 VA outcomes have shown comparable improvements through training using VR applications. Likewise, Rajavi et al, 49 Žiak et al, 16 Elhusseiny et al, 69 and Rajavi et al 50 have also made VA improvements, which reflected a promising application value for further research on this topic.…”
Section: Resultsmentioning
confidence: 80%
“…Among total references, the majority (16/48, 33.33%) used commercial standalone VR headset in their studies due to specific functions provided by the headsets. Oculus Rift was used by Nesaratnam et al, 75 Turnbull & Phillips, 82 Žiak et al, 16 Halička et al, 55 Jiménez-Rodríguez et al, 56 Jhangian et al, 58 and Godinez et al 80 This kind of headset provided VR experience without considering space constraints as the headset was a wireless type. HTC Vive was used by Hurd et al, 53 Martín et al, 68 Mehringer et al, 78 Lin & Chou 57 and Panfili et al, 65 while HTC Vive Pro Eye was used by Yeh et al 77 Although the HTC Vive series headsets were wire-connected, they provided high-resolution images while eye tracking functions were found with the Pro Eye model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent development in the creation of new pleoptic techniques is the use of VR, which allows for full dichoptic imaging, where each eye sees something slightly different, especially concerning minute details that are essential for controlling the game in question, as well as fundamentally superior 3D imaging. In Halička et al ( 41 ), conducted dichoptic vision therapy using the computer game Diplopia Game (Vivid Vision, USA), which has been played within an Oculus Rift DK2 VR headset (Oculus VR, USA). The workout required 8 h of training every cycle, which was completed twice a week.…”
Section: Vr Exercises For Prevention and Control Of Human Ocular Dise...mentioning
confidence: 99%
“…For this reason, VR devices have been proposed as potential tools for the training of binocular vision in amblyopia [ 14 ], specifically for the training of stereoscopic vision [ 15 ]. Some authors have previously studied the improvement of stereoscopic vision after VR treatment in adults with anisometropic amblyopia [ 16 , 17 ], using, in some cases, functional magnetic resonance to observe the real neural impact [ 18 ], and also in stereoblind subjects [ 19 , 20 ]. This is possibly due to the plasticity of the adult visual system.…”
Section: Introductionmentioning
confidence: 99%